Plan de marketing para la empresa “DOMIICELL” servicio técnico-venta de celulares y accesorios en la ciudad de Loja, año 2023 - Pineda Macas, Johanna Stefania (2023)
The purpose of marketing will always be to sell through some strategies, carrying out this titling work was justified because it was necessary to improve the situation of the company "DOMIICELL" that required the proposal of a marketing plan that guides its actions in order to improve your income. The approach that was applied for the present work of study was the qualitative investigation, transversal the descriptive method, the techniques were the observation, interview and the survey. The study was based on two main objectives: first, the situational diagnosis of the company, observing its internal, external and competitive environment to find its strengths, opportunities, threats and weaknesses. The internal analysis of the EFI matrix with the data from the surveys and interviews that yielded a value of 2.74, which indicates that the company works at a level where the strengths outweigh the problems. From the external analysis taking into account the impact of political, economic, social, technological and environmental aspects, a value of 2.77 was obtained in the EFE matrix, which indicates that the company takes advantage of the opportunities of the environment while limiting the effects of the threats. In addition, a value of 2.80 was obtained in the MPC, which translates into a solid position in the market. To achieve the second objective, marketing strategies were determined, in relation to the high impact matrix, obtaining three objectives: position the company's brand in social networks, retain potential customers and train staff, the budget to be executed is $2,855. Finally, conclusions and recommendations are issued in light of the results of the investigation. Thanks to all this, the company "DOMIICELL" will be able to position itself in the market and achieve its goals.